O134 The dysfunction of autonomic nervous system in children with paroxysmal disorders. Issue 9 (September 2017) - Gergont, Aleksandra
Abstract : Introduction: Autonomic nervous system (ANS) involvement in children with paroxysmal events can be seen at multiple levels, including epileptic ictal and postictal symptoms, status epilepticus, non-epileptic spells, side effects of antiepileptic drugs and vagus nerve stimulation. Autonomic testing combines a battery of tests serving to define the severity of the problem. Aim: The aim of the study was to present current knowledge regarding the involvement of ANS in children with paroxysmal disorders. Material and methods: Using key words ANS, epilepsy and syncope the search was performed in collections of Elsevier and Springer Journals, as well as PubMed. Results: Manifestation of ANS dysfunctions may comprise a clinical spectrum of symptoms, including apnea, arrhythmia, hypotension and aspiration. Certain pediatric epilepsy syndromes present with a unique prominence of autonomic signs and symptoms (Panayiotopoulos syndrome). Autonomic dysfunction has been hypothesized in children with channelopathies such as Dravet syndrome. In adolescents with syncope, autonomic testing can help to stratify the risk of future episodes and to guide treatment decisions. Cardiovagal testing has been demonstrated in a number of paroxysmal disorders to be a marker of autonomic dysfunction. Conclusions: Recognition of the diverse autonomic manifestations of epilepsy and non-epileptic spells would enhance early diagnosis and appropriate management, ultimately improving quality the of life of the affected patients. Symptoms of ANS dysregulation may warning as for life threatening conditions, so they should be included as a part of medical history and physical examination.